UWB Transmission Waveform Application for in an Indoor Localization System - Mankong, Thanadon; Promwong, Sathaporn; Bunlaksananusorn, Chanin (My University, 2024)
Nowadays, the indoor localization systems had been widely utilized. The popular use of localization system is the global position system (GPS). However, the system fails in particular environments such as indoors because low received signal power. It is not appropriate to take a position. The indoor localization system was used to assist in finding a position in an indoor environment. There are several techniques used to evaluate. Technique trilateration model is a technique of geometric. This technique leverages circular intersections to estimate target positions. The circles are derived from a set of reference positions. This paper studies on indoor positioning in line of sight (LOS) using by IEEE 802.15.4 standard in ultra wideband option which this study employs trilateration to estimate the position of target objects. Biconical antennas with vertical polarization serve as both transmitting and receiving elements. The evaluation is conducted using a vector network analyzer (VNA) across a frequency range of 3GHz to 11GHz. The positioning accuracy will be assessed in terms of distance error.
Keywords: impulse radio; indoor localization; trilateration technique; UWB; UWB-IR